On the conferment of an Honorary Degree - Depretis, Giancarlo Mario (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Presentation address by Professor Giancarlo Depretis on the occasion of the conferment of the honorary degree in European and American Modern Languages and Literatures of the University of Turin upon writer Mario Vargas Llosa